Borylation of Unactivated Aryl Chlorides under Mild Conditions by Using Diisopropylaminoborane as a Borylating Reagent. Issue 19 (11th April 2014) - Guerrand, Hélène D. S.; Marciasini, Ludovic D.; Jousseaume, Mélissa; Vaultier, Michel; Pucheault, Mathieu
Abstract The synthesis of arylboronic ester derivatives from aryl chlorides by using aryl(amino)boranes is described. Palladium‐catalyzed coupling between aryl chlorides and diisopropylaminoborane leads to the formation of a CB bond under mild conditions. A wide range of functional groups are tolerated, making this method particularly useful for the borylation of functionalized aromatics.